68Ga-PSMA–Avid Intranasal Solitary Fibrous Tumor. (20th April 2023) - Riaz, Saima; Priftakis, Dimitrios; Afaq, Asim; Kayani, Irfan; Bomanji, Jamshed
Abstract: The utility of molecular imaging in solitary fibrous tumors has not been fully established. We present a rare case of recurrent intranasal solitary fibrous tumor incidentally localized on 68 Ga-PSMA PET/CT scan, which turned out to be metabolically inactive on 18 F-FDG PET/CT.